Accuracy Estimation of TOPCON GRS-1 GNSS Receiver Parameters in Static and Dynamic Mode - Belinska, V.; Kluga, A.; Kluga, J.; Bricis, A. (Elektronika ir Elektrotechnika, 2014)
This article describes some of the testing results for TOPCON Geodetic Rover System’s (GRS-1) Global Navigation Satellite System (GNSS) receiver in static and dynamic modes. First of all, our attention was focused on estimation of accuracy for GRS-1 receiver in static mode. Then we tried to evaluate these characteristics of the receiver in dynamic mode. Also, the article includes the results of inertial system possibilities to improve vehicle position estimates and movement parameters when the satellite signal is unavailable. DOI: http://dx.doi.org/10.5755/j01.eee.20.2.6385